Increasing the Growth and Production of Purple Eggplant (Solanum melongena L.) by Providing Liquid Organic Fertilizer (POC) from Market Waste Enriched with Maja Fruit - Willi; Elfi Indrawanis; Chairil Ezward (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Eggplant is widely appreciated as a food source across all levels of society and is among the most popular dishes in various communities. Therefore, the growth and production of eggplant require fertilizers to supply essential nutrients. Fertilizer materials can utilize potential waste, such as market waste. To increase the phosphorus content in liquid organic fertilizer, it can be enriched with maja fruit. Liquid organic fertilizer derived from market waste, consisting of vegetables and fruits, contains high levels of nitrogen, which is a fundamental component of protein and chlorophyll in plants. The purpose of this study was to determine the effect of applying liquid organic fertilizer (POC) made from market waste enriched with maja fruit on the growth and production of purple eggplant (Solanum melongena L.). The experimental research employed a Non-Factorial Completely Randomized Design (CRD). The treatments were as follows: A0 – no POC application; A1 – POC concentration of 100 ml per liter of water; A2 – POC concentration of 200 ml per liter of water; and A3 – POC concentration of 300 ml per liter of water. The results showed significant effects on flowering and harvest age. The treatment that produced the best results across all parameters was A2, which involved applying market waste POC enriched with maja fruit at a concentration of 200 ml per liter of water. However, this treatment did not significantly affect plant height (cm), fruit weight per plant (grams), or the number of fruits per plant. The liquid organic fertilizer produced contains high levels of essential nutrients, such as boron (B) and iron (Fe), which accelerate the generative phase, including flowering, thereby advancing the plant's harvest age. Reason: The text was revised to improve clarity, coherence, and technical accuracy. Grammar, punctuation, and spelling errors were corrected. Vocabulary was enhanced for better readability and precision, and sentence structure was refined to ensure a smooth flow and a professional tone appropriate for scientific writing.